2015
DOI: 10.1080/01635581.2015.1029637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mediterranean Diet Intervention on Anti- and Pro-Inflammatory Eicosanoids, Epithelial Proliferation, and Nuclear Morphology in Biopsies of Normal Colon Tissue

Abstract: This randomized trial evaluated the effects of intervention with either a Healthy Eating or a Mediterranean diet on colon biomarkers in 120 healthy individuals at increased colon cancer risk. The hypothesis was that eicosanoids and markers of proliferation would be favorably affected by the Mediterranean diet. Colon epithelial biopsy tissues and blood samples were obtained at baseline and after six months of intervention. Colonic eicosanoid concentrations were evaluated by HPLC-MS-MS, and measures of epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Here we found that NSAID use reduced PTGS2, but not PTGS1 mRNA expression levels (Table 1). These findings indicate that PTGS2 may contribute at least partially to PGE 2 production in the normal colon since NSAID use significantly decreased colon PGE 2 concentrations in biopsy samples from this study, as we published previously (29). Cholesterol medication use was significantly associated with reduced mRNA expression of PTGES1, and PTGES1 is the synthase that associates with PTGS2 (Table 1).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here we found that NSAID use reduced PTGS2, but not PTGS1 mRNA expression levels (Table 1). These findings indicate that PTGS2 may contribute at least partially to PGE 2 production in the normal colon since NSAID use significantly decreased colon PGE 2 concentrations in biopsy samples from this study, as we published previously (29). Cholesterol medication use was significantly associated with reduced mRNA expression of PTGES1, and PTGES1 is the synthase that associates with PTGS2 (Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the effects of dietary fat discussed above, the antioxidant effects of higher consumption of fruits and vegetable also may work to reduce production of inflammatory mediators (15). Despite this, we previously reported that a Mediterranean intervention did not significantly affect colon PGE 2 (16). PGE 2 concentrations at the time of biopsy, however, might not reflect the capacity of the tissue to produce PGE 2 since PGE 2 can be rapidly formed and degraded in cells.…”
Section: Introductionmentioning
confidence: 80%
“…Three frozen biopsies were pulverized in liquid nitrogen, and pooled homogenates were prepared in buffered saline containing indomethacin as described previously (20, 21). Deuterated internal standards were added before extraction and analysis of eicosanoids (20). Protein in a portion of the homogenate was determined by the Bradford assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Proliferation in colon biopsies was determined as described previously (20) using IHC staining for Ki67 with antibodies from Leica Biosystems. Positive nuclei were visualized with horseradish peroxidase–conjugated streptavidin and 3,3′-diaminobenzidine substrate.…”
Section: Methodsmentioning
confidence: 99%
“…The study of the modulation of the inflammatory state through nutrigenomics would seem to identify the MD as preventive for CDDs [125,126]. Some components of the MD, such as ω3, are known to alter the expression of chemical mediators of the inflammatory state [117,127].…”
Section: From Disease To Health Statusmentioning
confidence: 99%